2010
DOI: 10.1128/aem.01178-10
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Genes Encoding Cytochrome Oxidases and Quinol Monooxygenase Blocks the Aerobic-Anaerobic Shift in Escherichia coli K-12 MG1655

Abstract: The constitutive activation of the anoxic redox control transcriptional regulator (ArcA) in Escherichia coli during aerobic growth, with the consequent production of a strain that exhibits anaerobic physiology even in the presence of air, is reported in this work. Removal of three terminal cytochrome oxidase genes (cydAB, cyoABCD, and cbdAB) and a quinol monooxygenase gene (ygiN) from the E. coli K-12 MG1655 genome resulted in the activation of ArcA aerobically. These mutations resulted in reduction of the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 53 publications
(124 reference statements)
5
49
1
Order By: Relevance
“…Data represent the averages from four experiments, and the standard deviation values are indicated. and coworkers (41). Our results are also in accordance with the previous findings that despite the aerobic growth conditions, an ArcA-P expression profile was observed in mutant strains lacking both cytochrome bo and cytochrome bd terminal oxidases (42), the ubiG gene (43), or the three terminal cytochrome oxidase genes (cydAB, cyoABCD, and cbdAB) and a quinol monooxygenase gene (ygiN) (41).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Data represent the averages from four experiments, and the standard deviation values are indicated. and coworkers (41). Our results are also in accordance with the previous findings that despite the aerobic growth conditions, an ArcA-P expression profile was observed in mutant strains lacking both cytochrome bo and cytochrome bd terminal oxidases (42), the ubiG gene (43), or the three terminal cytochrome oxidase genes (cydAB, cyoABCD, and cbdAB) and a quinol monooxygenase gene (ygiN) (41).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the authors concluded that inhibition of ArcB phosphatase activity mediated by fermentation products, such as acetate, may be the dominant mechanism for regulating ArcB and, thereby, ArcA activity instead of the redox state of the ubiquinone pool (26). However, the 2-fold difference in total ubiquinone between anaerobiosis and full aerobiosis contrasts the ϳ5-fold increase reported earlier (25,39,41,44,45) and weakens the above-mentioned conclusion. Moreover, this mode of ArcB regulation has been discarded in earlier in vivo and in vitro studies that demonstrate that fermentation products, such as acetate and lactate, have no effect on the ArcB phosphatase activity (12) and do not act as direct signals for activation of ArcB E=°ϭ ϩ100 mV) constitute the major quinones in the respiratory chain of E. coli.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Similar shifts in metabolism were observed for an E. coli mutant strain deleted for the three terminal cytochrome oxidase genes and therefore unable to use oxygen for oxidative phosphorylation and ATP synthesis. In this mutant, genes for anaerobic respiration were induced even under oxic conditions, as were glycolysis-related genes, probably to sustain ATP generation through substrate-level phosphorylation (88).…”
Section: Discussionmentioning
confidence: 99%